Enhancing microbial population and biomass of water spinach grown in tailing and inceptisols by manure amendment - Hindersah, Reginawanti; Suryatmana, Pujawati; Herdiyantoro, Diyan; Hamdani, Jajang Sauman (Jurnal AGRO, 2025)
The impact of tailings accumulated on agricultural land is the loss of soil profile and decreased soil quality, making plants difficult to grow. This study aimed to observe the effect of cow dung manure (CM) doses to gold mine tailings on total fungal and bacterial populations of soil surrounding roots and water spinach biomass and to analyze the correlation between fungal and bacterial populations with water spinach growth parameters. The experiment was designed in a randomized block design with five treatments and five replications. The treatments included without CM (control) and 5, 10, 15, and 20% of CM in tailing. Similar treatments were added to plants grown in mineral soil, i.e. Inceptisols. The results determined the retarded plant growth in tailing compared to that in Inceptisols. The plant grown in tailing was more responsive to manure amendment. The CM increased total fungal and bacterial populations in the soil around the roots, plant height, leaf number, stem thickness, wet weight, and dry weight of intact plants. Applying 5% of CM caused better growth of water spinach than other treatments. Total fungal and bacterial populations were strongly correlated with water spinach height and dry weight. ABSTRAK Dampak negatif penumpukan tailing di lahan pertanian adalah hilangnya profil tanah dan penurunan kualitas tanah sehingga tanaman sulit tumbuh. Penelitian ini bertujuan untuk mengobservasi pengaruh pemberian dosis pupuk kotoran sapi (PKS) pada tailing tambang emas terhadap populasi jamur dan bakteri total biomassa kangkung darat (Ipomoea reptans (L.) Poir.) serta menganalisis korelasi antara populasi jamur dan bakteri di tanah sekitar perakaran dengan parameter pertumbuhan kangkung. Percobaan pot di rumah kaca disusun dalam rancangan acak kelompok dengan lima perlakuan dan lima ulangan. Perlakuan percobaan adalah tanpa dan dengan penambahan 5, 10, 15 dan 20% PKS ke dalam tailing. Perlakuan yang sama diberikan pada tanaman kangkung dengan tanah Inceptisol. Hasil percobaan menunjukkan bahwa pertumbuhan kangkung di tailing terhambat dibandingkan di tanah Inceptisols, tetapi tanaman di tailing lebih responsif terhadap aplikasi PKS. Pupuk kotoran sapi mampu meningkatkan populasi jamur dan bakteri total di sekitar perakaran, tinggi tanaman, jumlah daun, ketebalan batang, bobot basah serta bobot kering tanaman di tailing. Pemberian 5% PKS lebih meningkatkan pertumbuhan tanaman kangkung dibandingkan dengan perlakuan lainnya. Populasi jamur dan bakteri masing-masing berkorelasi positif dengan hubungan yang sangat kuat dengan bobot kering serta tinggi tanaman kangkung. Percobaan ini menjelaskan bahwa bahan organik penting untuk memperbaiki kualitas tailing dan pertumbuhan tanaman.